Interdisciplinary Peripartum Management of Acute Respiratory Distress Syndrome with Extracorporeal Membrane Oxygenation – a Case Report and Literature Review - Weyrich, J.; Bogdanski, R.; Ortiz, J. U.; Kuschel, B.; Schneider, K. T. M.; Lobmaier, S. M. (Geburtshilfe und Frauenheilkunde, 2016)
Extracorporeal membrane oxygenation (ECMO) is increasingly used for the management of acute severe cardiac and respiratory failure. One of the indications is acute respiratory distress syndrome (ARDS) for which, in some severe cases, ECMO represents the only possibility to save lives. We report on the successful long-term use of ECMO in a postpartum patient with recurrent pulmonary decompensation after peripartum uterine rupture with extensive blood loss.
Keywords: ECMO; ARDS; uterine rupture; vaginal birth after 2 Caesarean sections; TRALI; SIRS